Asymmetric rhenium tricarbonyl complexes show superior luminescence properties in live cell imaging. Issue 5 (23rd December 2016) - Raszeja, Lukasz J.; Siegmund, Daniel; Cordes, Anna L.; Güldenhaupt, Jörn; Gerwert, Klaus; Hahn, Stephan; Metzler-Nolte, Nils
Abstract : Novel luminescent phenanthridinyl containing ReCO3 complexes with unusual asymmetric ligand design accumulate in the endoplasmic reticulum of living cancer cells. Abstract : The synthesis and photophysical properties of a novel series of rhenium tricarbonyl complexes based on tridentate phenanthridinyl-containing ligands are described. Photophysical data reveal beneficial luminescence behaviour especially for compounds with an asymmetric ligand set. These advantageous properties are not limited to organic solvents, but indeed also improved in aqueous solutions. The suitability of our new rhenium complexes as potent imaging agents has been confirmed by fluorescence microscopy on living cancer cells, which also confirms superior long-time stability under fluorescence microscopy conditions. Colocalisation studies with commercial organelle stains reveal an accumulation of the complexes in the endoplasmic reticulum for all tested cell lines.